Reducing traffic congestion through ride sharing in Bangladesh: a case study of Dhaka City - Mollah, Md Lokman Hossain (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2020.